Myths and Realities Relating to Development of the Arterial Valves - Robert H. Anderson; Timothy J. Mohun; Diane E. Spicer; Simon D. Bamforth; Nigel A. Brown; Bill Chaudhry; Deborah J. Henderson (Journal of Cardiovascular Development and Disease, 2014)
There is considerable confusion as to how best describe the components of the arterial valves. It is hardly surprising, therefore, that similar uncertainties apply to concepts for their development. In this review, we describe the anatomy of the arterial valves as seen in the postnatal heart. We suggest that their working components are best described as leaflets, housed in supporting arterial sinuses. The roots surrounding the leaflets, which are hinged in semilunar fashion, can then be defined as extending from a virtual ring at their base to the sinutubular junction. We also discuss the problems related to definition of the valvar “annulus”. Understanding the development of the arterial roots, which are formed in the central part of the embryonic outflow tract, is facilitated by considering the outflow tract itself as possessing three components, as opposed to the traditional “conus” and “truncus”. These three parts can be described as being distal, intermediate, and proximal. The distal part is separated to form the intrapericardial arterial trunks, while the proximal part becomes the ventricular outflow tracts. It is the intermediate component that houses the developing arterial valves, and their supporting valvar sinuses. The distal parts of the cushions that separate the outflow tract into aortic and pulmonary components, along with the intercalated cushions, excavate to form the leaflets. The walls of the sinuses are formed by growth of non-myocardial tissues from the heart-forming area. We then show how these features can be used to interpret the anatomy and development of congenitally malformed arterial valves.